Gender Inequality on the Labour Market in Russia - АнтонченковаСветлана Валентиновна (Journal of Economic Sociology, 2010)
The goal of the paper is to analyze the current situation on the labour market in Russia focusing on the gender inequality. The object of the study is all employed population of the country. The subject of the study is the gender inequality particularly gender segregation and gender discrimination on the labour market. The analysis is based on the Goskomstat data and RLMS data set.